Demand management processes to improve access to cognitive-behavioral therapies for anxiety disorders: a grounded theory study - Carrier, Jean-Daniel; Gallagher, Frances; Vanasse, Alain; Roberge, Pasquale (Frontiers in Health Services, 2024)
Introduction Anxiety disorders are impactful mental health conditions for which evidence-based treatments are available, notably cognitive-behavioral therapies (CBTs). Even when CBTs are available, demand-side factors limit their access, and actors in a position to perform demand management activities lack a framework to identify context-appropriate actions. Methods We conducted a constructivist grounded theory study in Quebec, Canada, to model demand management targets to improve access to CBTs for anxiety disorders. We recruited key informants with diverse experiences using purposeful, then theoretical sampling. We analyzed data from 18 semi-directed interviews and 20 documents through an iterative coding process centered around constant comparison. Results The resulting model illustrates how actors can target clinical-administrative processes fulfilling the demand management functions of detection, evaluation, preparation, and referral to help patients progress on the path of access to CBTs. Discussion Modeling clinical-administrative processes is a promising approach to facilitate leveraging the competency of actors involved in demand management at the local level to benefit public mental health.